Accuracy analysis and improvement of the state‐queuing model for the thermostatically controlled loads. Issue 5 (24th January 2017) - Bao, Yu‐Qing; Hu, Minqiang; Hong, Ying‐Yi; Chen, Pei‐Pei; Ju, Jia‐Qi; Ma, Gang
Abstract : The development of smart metering technologies makes it possible to apply the thermostatically controlled loads (TCLs) into the demand response programs such as direct load control. To characterise the dynamics of a large number of TCLs, the computationally efficient sate‐queuing (SQ) model is designed in some recent research works. However, very few attentions have been given to its accuracy. This study reviews the existing SQ modelling approach, and reveals its limitations in the accuracy by comprehensive comparison and analysis. To improve the accuracy of the SQ model, a modification method is specially designed based on the optimisation technique. Numerous simulation results verify the effectiveness of the proposed method.